Strategic risk management : a practical guide to portfolio risk management - Iverson, David (Singapore : Wiley, 2013)
A comprehensive guide to the key investment decisions all investors must make and how to manage the risk that entails Since all investors seek maximize returns balanced against acceptable risks, successful investment management is all about successful risk management. Strategic Risk Management uses that reality as a starting point, showing investors how to make risk management a process rather than just another tool in the investor's kit. The book highlights and explains primary investment risks and shows readers how to manage them across the key areas of any fund, including investment objecti.
Includes bibliographical references and index.
Print version record.
Keywords: Financial risk management; Portfolio management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Financial risk management; Portfolio management; Electronic books